Intergenerational Environmental Justice - Paz Landeira, Florencia (EUNOMÍA. Revista en Cultura de la Legalidad, 2025)
This article examines intergenerational environmental justice in light of children’s emergence as leading actors in climate litigation. It surveys theoretical critiques that move beyond the traditional linear and paternalistic perspective, incorporating insights from queer theory and decolonial approaches. The notion of «generation» is also revisited through sociological and anthropological lenses that highlight the coexistence of multiple cohorts in the present, while the climate crisis is shown to demand an immediate allocation of responsibilities, rather than the mere safeguarding of a hypothetical future. The article ultimately advances a post-paternalist framework that recognises the agency of children and weaves together critical temporalities with the urgency and structural inequalities that define today’s ecological landscape.